Training Needs Assessment on Blended Learning Model Management to Improve Teachers’ Competence - Rustiyana Rustiyana; Achmad Sanusi; N. Dede Khoeriah; Daeng Arifin (Publikasi Indonesia, 2022)
This research is motivated by the existence of gaps and problems in the low competence of teachers in Indonesia. The implementation of blended learning model training is a solution to improve teacher competence. The training will run effectively, efficiently as the target if it can implement training management properly. The first stage of training management is Training Needs Assessment. Training Needs Assessment (TNA) is the first stage in training management that determines whether the next stage is successful or not. TNA is also a diagnostic process in order to be able to determine/take pictures of the problems that are currently being faced and how the challenges will be in the future and both of these things that must be fulfilled in the implementation of the training. The purpose of this study is to describe and analyze TNA in blended learning model training management in improving teacher competence at the Center for the Development and Empowerment of Science Educators and Educators (PPPPTK) Bandung, West Java. The research approach uses a qualitative approach with a case study method. The results showed that PPPPTK IPA in implementing blended learning model training management in improving teacher competence had implemented TNA with the stages of Analyze training needs and Identify training objectives and criteria.